2013
DOI: 10.1016/j.bbamcr.2012.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts in post-infarction inflammation and cardiac repair

Abstract: Fibroblasts are the predominant cell type in the cardiac interstitium. As the main matrix-producing cells in the adult mammalian heart, fibroblasts maintain the integrity of the extracellular matrix network, thus preserving geometry and function. Following myocardial infarction fibroblasts undergo dynamic phenotypic alterations and direct the reparative response. Due to their strategic location, cardiac fibroblasts serve as sentinel cells that sense injury and activate the inflammasome secreting cytokines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
178
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(185 citation statements)
references
References 121 publications
(151 reference statements)
7
178
0
Order By: Relevance
“…(Myo)fibroblasts have different roles in the different phases. 4,10 In the initial phase, the fibroblasts act as local immune modulators and are the main effectors of fibrogenesis. 1,[4][5][6]20 In the subsequent proliferative phase of healing, fibroblasts further differentiate into myofibroblasts that not only have an augmented matrixsynthetic phenotype but also express the contractile protein α-SMA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(Myo)fibroblasts have different roles in the different phases. 4,10 In the initial phase, the fibroblasts act as local immune modulators and are the main effectors of fibrogenesis. 1,[4][5][6]20 In the subsequent proliferative phase of healing, fibroblasts further differentiate into myofibroblasts that not only have an augmented matrixsynthetic phenotype but also express the contractile protein α-SMA.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Cardiac fibroblasts, which account for up to 70% of the cells present in the myocardium, regulate extracellular matrix (ECM) turnover, and have an essential role in cardiac homeostasis. Fibroblasts are more resistant to ischemia than cardiomyocytes, [4][5][6] and prolonged myocardial ischemia results in death of particularly the cardiomyocytes, whereas the fibroblasts survive. Fibroblasts have therefore been proposed to be a therapeutic target to influence the healing process of the infarcted myocardium.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…CXCL-1, 2, 5 and 8), and express specific neutrophil-binding adhesion molecules including ICAM-1 and E-selectin [88,[90][91][92][93], as well as the matricellular protein TN-C [94]. Thus, CF may contribute to the inflammatory milieu that occurs in the myocardium early after MI [10,95]. In addition to this inflammatory response, we [7,88,93,94,[96][97][98] and others [61,99,100] have demonstrated that CF alter the balance of cardiac ECM turnover in favour of degradation in response to IL-1; for example by increasing secretion of MMPs, decreasing collagen synthesis and decreasing expression of profibrotic factors (e.g.…”
Section: Interleukin-1mentioning
confidence: 99%